Missed opportunities to vaccinate children admitted to a paediatric tertiary hospital. Issue 7 (9th January 2007) - Walton, Suzanne; Elliman, David; Bedford, Helen
Abstract : Background: Inequalities in vaccine uptake exist. Studies suggest paediatric inpatients have lower rates of immunisation uptake than the general population. Various UK policies advocate opportunistic immunisation. Aim: To evaluate practice within a paediatric tertiary hospital in identifying and facilitating vaccination of inpatients who were not fully immunised. Methods: Case notes for 225 inpatients were examined. Thirty staff of various professions and grades were interviewed. Policies, forms and documents used in the hospital were reviewed. Results: Immunisation status was recorded for 71% of children admitted, but for 69% of these immunisations were documented as "up-to-date" without any further information recorded. At least 20% of inpatients were incompletely immunised, but very little was done to facilitate vaccination. There was no training for staff either in giving advice or in administering vaccines and staff views differed regarding the hospital's role in immunisations. While there were guidelines for specific groups of patients, there were no general immunisation policies. Incorrect and out-of-date immunisation schedules were found on documents. Conclusions: Opportunities to immunise children continue to be missed by all levels of health care service provision. Tertiary centres have a role to play in supporting primary care services to ensure that these vulnerable children are appropriately immunised. Measures are being taken to address the problems identified in this study and we strongly suspect that other hospitals in the UK ought to be confronting these issues as well.